2013
DOI: 10.5664/jcsm.3166
|View full text |Cite
|
Sign up to set email alerts
|

Air Leak during CPAP Titration as a Risk Factor for Central Apnea

Abstract: BRIEF SUMMARYCurrent Knowledge/Study Rationale: CPAP initiation has been associated with the emergence of central apneas. This study aims to determine the relationship, if any, between CPAP mask leak and central apneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…CPAP was minimally but significantly higher in those with CPAP emergent CSA but the magnitude of difference was so small (less than 1 cmH 2 O) that this difference is not clinically meaningful. The authors also found that air leak was significantly higher in patients with CPAP emergent CSA as has been observed in a prior study where the authors speculated that this observation might be mechanistically important (by leading to greater sleep disruption and/or greater carbon dioxide clearance both of which could promote central events) (10). Further study to determine whether efforts to reduce air leak result in amelioration of CPAP emergent CSA (persistent or late emergent) are warranted.…”
supporting
confidence: 57%
“…CPAP was minimally but significantly higher in those with CPAP emergent CSA but the magnitude of difference was so small (less than 1 cmH 2 O) that this difference is not clinically meaningful. The authors also found that air leak was significantly higher in patients with CPAP emergent CSA as has been observed in a prior study where the authors speculated that this observation might be mechanistically important (by leading to greater sleep disruption and/or greater carbon dioxide clearance both of which could promote central events) (10). Further study to determine whether efforts to reduce air leak result in amelioration of CPAP emergent CSA (persistent or late emergent) are warranted.…”
supporting
confidence: 57%
“…The physiological cause of this finding is not clear and beyond the scope of this study but may suggest causes other than anatomical for the high AHI FLOW . Excessive air leak can cause central apnea during positive pressure titration, 11 and by extension may occur for the same reason during chronic PAP treatment, but was not the cause in our patients as excessive leak was part of our exclusion criteria. However, this finding, along with high AHI on the titration study ( Table 1) suggest a possible role for treatment emergent sleep apnea and ventilatory instability leading to high residual AHI FLOW , primarily on manual scoring.…”
Section: Discussionmentioning
confidence: 99%
“…Air leak with the face mask can contribute to discomfort, disrupt sleep, promote patient-ventilator dyssynchrony, and foster unstable breathing patterns. 10 Independent of mechanical support, airflow directed to the face may reduce dyspnea via trigeminal reflexes, 11 potentially improving tolerance of NIV via the helmet. Sedatives administered to promote patient tolerance of NIV may introduce associated risks, including oversedation, aspiration, and delirium.…”
mentioning
confidence: 99%